Contests with deadly weapons: telson sparring in mantis shrimp (Stomatopoda) - Green, P. A. (Biol Lett, 2015)
Mantis shrimp strike with extreme impact forces that are deadly to prey. They also strike conspecifics during territorial contests, yet theoretical and empirical findings in aggressive behaviour research suggest competitors should resolve conflicts using signals before escalating to dangerous combat. We tested how Neogonodactylus bredini uses two ritualized behaviours to resolve size-matched contests: meral spread visual displays and telson (tailplate) strikes. We predicted that (i) most contests would be resolved by meral spreads, (ii) meral spreads would reliably signal strike force and (iii) strike force would predict contest success. The results were unexpected for each prediction. Contests were not resolved by meral spreads, instead escalating to striking in 33 of 34 experiments. The size of meral spread components did not strongly correlate with strike force. Strike force did not predict contest success; instead, winners delivered more strikes. Size-matched N. bredini avoid deadly combat not by visual displays, but by ritualistically and repeatedly striking each other's telsons until the loser retreats. We term this behaviour ‘telson sparring', analogous to sparring in other weapon systems. We present an alternative framework for mantis shrimp contests in which the fight itself is the signal, serving as a non-lethal indicator of aggressive persistence or endurance.